Flexible foraging movements of Leatherback turtles across the North Atlantic Ocean - Graeme Hays; V Hobson; J Metcalfe; D Righton; D Sims (2006)
Some marine species have been shown to target foraging at particular hotspots of high prey abundance. However, we show here that in the year after a nesting season, female leatherback turtles (Dermochelys coriacea) in the Atlantic generally spend relatively little time in fixed hotspots, especially those with a surface signature revealed in satellite imagery, but rather tend to have a pattern of near continuous traveling. Associated with this traveling, distinct changes in dive behavior indicate that turtles constantly fine tune their foraging behavior and diel activity patterns in association with local conditions. Switches between nocturnal vs. diurnal activity are rare in the animal kingdom but may be essential for survival on a diet of gelatinous zooplankton where patches of high prey availability are rare. These results indicate that in their first year after nesting, leatherback turtles do not fit the general model of migration where responses to resources are suppressed during transit. However, their behavior may be different in their sabbatical years away from nesting beaches. Our results highlight the importance of whole-ocean fishing gear regulations to minimize turtle bycatch.